2020
DOI: 10.1093/cid/ciaa823
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Costs of Injection Drug Use in Florida

Abstract: People who inject drugs (PWID) experience significant injection related infections (IRI) at significant healthcare system cost. This article utilizes and validates an ICD-10 based algorithm to estimate hospitalized PWID populations, assess the total statewide morbidity of IRI among PWID, and calculates associated costs of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…Infectious complications of injection drug use have a severe financial impact on the health‐care system [ 17 , 18 ] and between 2002 and 2012, the cost of OUD‐related infections more than tripled [ 7 ]. Previous reports in the literature that have reviewed hospitalization outcomes have revealed this financial impact on county safety‐net health‐care systems and state‐wide impact [ 17 , 18 ] but none, to our knowledge, have investigated hospital outcomes in a multi‐state private, for‐profit health‐care system. High‐risk injection behaviors, such as sharing or re‐using injection equipment, can contribute to infectious complications [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Infectious complications of injection drug use have a severe financial impact on the health‐care system [ 17 , 18 ] and between 2002 and 2012, the cost of OUD‐related infections more than tripled [ 7 ]. Previous reports in the literature that have reviewed hospitalization outcomes have revealed this financial impact on county safety‐net health‐care systems and state‐wide impact [ 17 , 18 ] but none, to our knowledge, have investigated hospital outcomes in a multi‐state private, for‐profit health‐care system. High‐risk injection behaviors, such as sharing or re‐using injection equipment, can contribute to infectious complications [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrate that PWID admissions come at great social and economic cost to Florida and nationwide. 13,15 Limited billing for PCS-SAT modalities through analysis of billing and coding records in this statewide sample suggests major gaps exist during inpatient treatment of underlying SUD. 13,16 Other studies suggest similar de ciencies in implementation of best practices for hospitalized PWID.…”
Section: Discussionmentioning
confidence: 96%
“…13,15 Limited billing for PCS-SAT modalities through analysis of billing and coding records in this statewide sample suggests major gaps exist during inpatient treatment of underlying SUD. 13,16 Other studies suggest similar de ciencies in implementation of best practices for hospitalized PWID. A national survey of hospitalists indicated that while 84.5% reported "often or always" caring for patients with opioid use disorder (OUD), 88.9% "rarely or never" initiated buprenorphine in the inpatient setting.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations